Influence of understorey diversity on wildlife at the coal mining reclamation area in South Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nugroho Y, Supandi, Suyanto, Matatula J, Wirabuana PYAP. 2021. Influence of understorey diversity on wildlife at the coal mining reclamation area in South Kalimantan, Indonesia. Biodiversitas 22: 3736-3743. The existence of understorey at the coal mining reclamation area provides an important contribution to improve the environmental quality, especially the wildlife presence. Therefore, this study aims to determine the influence of understorey diversity on the wildlife at the coal mining reclamation area managed by the PT Borneo Indobara, South Kalimantan. This study used an ecological survey conducted in three reclamation areas classified based on the dominant species supporting the process, namely Paraserianthes falcataria (L-1), Anthocephalus cadamba (L-2), and a mixture of both species (L-3). The data were collected in two observation periods, namely August 2019 and August 2020. The results showed that at the first observation, ten families of understorey were observed from the survey and the highest diversity was recorded in L-2 (H'=1.71), followed by L-1 (H'=1.54), and L-3 (H'=1.27). Meanwhile, the wildlife in the first periods was only 6 species consisting of 3 birds, 2 reptiles, and 1 mammal. The number of species from every site was relatively equal at the first observation. In the second observation, the diversity of understorey considerably increased with approximately 22 families from the inventory. The highest understorey diversity in this observation was recorded in L-1 (H'=3.30), L-2 (H'=3.05), and L-3 (H'=3.04). Also, the higher understorey diversity was followed by the higher wildlife with 29 species, which consists of 26 birds, 2 reptiles, and 1 mammal. The highest appearance of bird species was in the L-1 with approximately 19 species, while the number of birds in L-2 and L-3 was relatively similar with approximately 15 species. Based on these results, the understorey diversity significantly contributes to improving the wildlife diversity at the coal mining reclamation area, primarily from the bird species.
Keywords: Coal mining; environmental quality; reclamation; understorey; wildlife